2018
DOI: 10.1111/jam.14148
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival ofEscherichia coliO157:H7 andSalmonellaTyphimurium in cowpats on pasture

Abstract: Aim: To investigate the survival of Escherichia coli O157:H7 and Salmonella Typhimurium in cowpats on pasture in a temperate Nordic climate. Methods and Results: The study consists of two parts, the first part using artificially created cowpats inoculated with E. coli O157:H7 and S. Typhimurium and the second part using cowpats from empty pastures on which cattle herds positive for E. coli O157:H7 had grazed 6 month previously. Artificial cowpats were created, placed in an outdoor field station in June, August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, it is reasonable to believe that a higher dry matter content will extend the survival period because of less exposure to UV radiation. This is supported by the ability of S. Typhimurium to be viable in cow pats for up to a year, depending on the decomposition influence by season and weather conditions [ 77 ]. Most slurries in Denmark applied to grassing areas or areas used for forage have a dry matter content of >5% and are often injected into the soil.…”
Section: Resulting Biosecurity Assessment Frameworkmentioning
confidence: 99%
“…However, it is reasonable to believe that a higher dry matter content will extend the survival period because of less exposure to UV radiation. This is supported by the ability of S. Typhimurium to be viable in cow pats for up to a year, depending on the decomposition influence by season and weather conditions [ 77 ]. Most slurries in Denmark applied to grassing areas or areas used for forage have a dry matter content of >5% and are often injected into the soil.…”
Section: Resulting Biosecurity Assessment Frameworkmentioning
confidence: 99%
“…infections have been associated with animal meat and raw milk, but these diseases can also be transmitted through contaminated water (Gruzdev et al, 2012). In addition, the two pathogens can survive for weeks or years in water and soil if environmental conditions, such as temperature, humidity and pH, are favourable (Nyberg et al, 2018). Recently, Ioanna et al (2018) have shown that populations of E. coli O157:H7 remained constant up to 28 days (>6Á20 log 10 CFU per g) and then slightly decreased until the 90 days of storage.…”
Section: Introductionmentioning
confidence: 99%